KONSTRUKSI MEDIA TERHADAP KASUS PENEMBAKAN DI LP CEBONGAN YOGYAKARTA (Analisis Framing Berita Kasus Penembakan di LP Cebongan di Portal Berita Kompas.com dan Detik.com) - Valen Liey; Seto Herwandito (Cakrawala Jurnal Penelitian Sosial, 2013)
Online Media have an excess of news delivery which is much faster than other conventional media such as newspapers. Every message is constructed by the media through a framing process or framing, that is being affected by a variety of interests, including the ideology of the media. Framing used by media to give emphasis on certain aspects in order to have a specific meaning for audiences according to the media interests.This research is done to know the news framing done by the Kompas.com and Detik.com towards the case of shooting at LP Cebongan. This research used constructsionist paradigm with qualitative approach. Analysis of the framing is done with the model analysis of Pan and Kosicki. The results show  that the framing is done by Detik.com towards LP Cebongan shooting is take sides/ support of Kopassus (the interests of media), meanwhile framing done Kompas.com still show some efforts of approaching on objectivity news coverage although tend to counter against Kopassus.  Keywords: Online Media, Framing, Detik.com, Kompas.com, LP Cebongan.